1990
DOI: 10.1017/s0954579400000596
|View full text |Cite
|
Sign up to set email alerts
|

Gaze behavior in autism

Abstract: Gaze behavior was assessed in 20 autistic individuels and in an age- and mental-age-matched mentally retarded control group. A time-sample technique was used to collect frequency of gaze directed at staff, at task, and elsewhere (at other) in familiar educational settings as subjects interacted with familiar staff and engaged in familiar educational activities. Gaze behaviors were sampled in each of three interactional conditions defined by staff-subject ratio. Significant effects of the intensity of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 24 publications
2
54
1
Order By: Relevance
“…The results indicate that individuals who have difficulties both with visceral regulation and right tympanic membrane compliance made fewer spontaneous eye gazes to the experimenter. The results support previous research reporting that individuals with atypical social behavior have difficulties with vagal regulation of the heart (Boyce et al, 2001;Denver, 2004;Monk et al, 2001;Toichi & Kamio, 2003) and in making spontaneous eye contact (Buitelaar, 1995;Horley, Williams, Gonsalvez, & Gordon, 2004;Volkmar & Mayes, 1990). The findings lead to an intriguing possibility that the joint assessment of the visceromotor (e.g., vagal regulation of the heart) and somatomotor (e.g., tympanic membrane compliance) components of the Social Engagement System may provide unique insight into the neural mechanisms mediating the difficulties in social behavior observed in several psychiatric disorders (e.g., autism spectrum disorder, social anxiety, selective mutism, and depression).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results indicate that individuals who have difficulties both with visceral regulation and right tympanic membrane compliance made fewer spontaneous eye gazes to the experimenter. The results support previous research reporting that individuals with atypical social behavior have difficulties with vagal regulation of the heart (Boyce et al, 2001;Denver, 2004;Monk et al, 2001;Toichi & Kamio, 2003) and in making spontaneous eye contact (Buitelaar, 1995;Horley, Williams, Gonsalvez, & Gordon, 2004;Volkmar & Mayes, 1990). The findings lead to an intriguing possibility that the joint assessment of the visceromotor (e.g., vagal regulation of the heart) and somatomotor (e.g., tympanic membrane compliance) components of the Social Engagement System may provide unique insight into the neural mechanisms mediating the difficulties in social behavior observed in several psychiatric disorders (e.g., autism spectrum disorder, social anxiety, selective mutism, and depression).…”
Section: Discussionsupporting
confidence: 90%
“…Research has demonstrated that several specific behavioral markers, including atypical eye contact, visual tracking, disengagement of visual attention, orienting to name, social smiling, social interest, and affect, can distinguish children who were later diagnosed with autism from other children by 12 months of age (Zwaigenbaum et al, 2005). Other studies have also demonstrated that children with autism spectrum disorder have poor eye contact and avoid gaze (Denver, 2004;Klin, Jones, Schultz, Volkmar, & Cohen, 2002;Ristic et al, 2005;Ruffman, Garnham, & Rideout, 2001;Volkmar & Mayes, 1990). The atypical pattern of eye gaze extends to individuals with Fragile X syndrome, a genetic disorder that results in developmental disability and difficulty in social engagement and communication behaviors (Hessl, Glaser, Dyer-Friedman, & Reiss, 2006).…”
Section: Current Studymentioning
confidence: 99%
“…Over the past two decades, systematic investigations have revealed how the children show disturbances in their ability to direct expressions of affect to another person, use facial expressions communicatively, and resonate to the emotions and bodily expressions of others~Bacon, Fein, Morris, Waterhouse, & Allen, 1998;Charman et al, 1997;Dawson, Hill, Spencer, Galpert, & Watson, 1990;Hobson & Lee, 1998;Landry & Loveland, 1988;Reddy, Williams, & Vaughan, 2002;Sigman, Kasari, Kwon, & Yirmiya, 1992;Wetherby & Prutting, 1984!. The children's lesser tendency to look toward others, not only in frequency but also in intensity of eye contact, is characteristic, and probably an early marker of the syndrome~e.g., Dawson, Osterling, Meltzoff, & Kuhl, 2000;DiLavore, Lord, & Rutter, 1995;Volkmar & Mayes, 1990;Wimpory, Hobson, Williams, & Nash, 2000!. In the domain of joint attention, children with autism show a reduced tendency to use eye contact and deictic gestures~e.g., pointing or showing! to coordinate attention and share experiences with social partners vis-à-vis objects or events in the world~McArthur & Adamson, 1996;Mundy, Sigman, Ungerer, & Sherman, 1986!, even though they are able to disengage and shift attention~Leekam, López, & Moore, 2000!, follow a head turñ Leekam, Hunnisett, & Moore, 1998!, and detect what is at the focus of someone's gazẽ Leekam, Baron-Cohen, Perrett, Milders, & Brown, 1997!. There is evidence that they are less likely to share affect in episodes of joint attention~Kasari et al, 1990!, they are more distinctive in their failure to point to and show rather than request things~Landry & Loveland, 1988;Mundy et al, 1986!, and they are limited in their responsiveness to others in settings that would typically elicit social referencing~Charman et al, 1997;Sigman et al, 1992!.…”
Section: The Case Of Autismmentioning
confidence: 99%
“…Sigman, Mundy, Sherman, & Ungerer, 1986; Van der Geest, Kemner, Camfferman, Verbaten, and Van Engeland, 2002;Volkmar & Mayes, 1990). Van der Geest et al (2002) found no difference between typically developing children and children with ASD, in terms of how much time was spent looking at pictures.…”
Section: Introductionmentioning
confidence: 99%